2010
DOI: 10.1016/j.joi.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of scholar collaboration on impact and quality of academic papers

Abstract: We study how scholar collaboration varies across disciplines in science, social science, arts and humanities and the effects of author collaboration on impact and quality of co-authored papers. Impact is measured with the aid of citations collected by papers, while quality is determined by the judgements expressed by peer reviewers. To this end, we take advantage of the dataset provided by the first-ever national research assessment exercise of Italian universities, which involved 20 disciplinary areas, 102 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(167 citation statements)
references
References 28 publications
8
139
3
1
Order By: Relevance
“…The findings on whole metrics for long term researchers are consistent with the findings of numerous studies for all researchers that have found that citation of articles increases as the number of authors increases (e.g., Herbertz, 1995;Glänzel, 2002;Leimu & Koricheva, 2005;Ma & Guan, 2006;Franceschet & Costantini, 2010;Levitt & Thelwall, 2010;Costas & van Bochove, 2012). This similarity in findings between long term and all researchers tends to suggest that the relationships between productivity and collaboration that apply to long tern researchers could also apply to short-term researchers and, in particular, that our findings may not be substantially different if short term researchers were included in the data.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The findings on whole metrics for long term researchers are consistent with the findings of numerous studies for all researchers that have found that citation of articles increases as the number of authors increases (e.g., Herbertz, 1995;Glänzel, 2002;Leimu & Koricheva, 2005;Ma & Guan, 2006;Franceschet & Costantini, 2010;Levitt & Thelwall, 2010;Costas & van Bochove, 2012). This similarity in findings between long term and all researchers tends to suggest that the relationships between productivity and collaboration that apply to long tern researchers could also apply to short-term researchers and, in particular, that our findings may not be substantially different if short term researchers were included in the data.…”
Section: Discussionsupporting
confidence: 87%
“…For example, a study using the whole of WoS, which is dominated by the sciences, found a general trend for articles with more co-authors to have higher mean citation counts (Costas & van Bochove, 2012). Similarly, a study of a sample of Italian articles, from a variety of areas of scholarship, found more highly authored articles to be both more highly cited and more highly rated by peer reviewers (Franceschet & Costantini, 2010). At the level of individual scientific subjects, each additional author, to a maximum of 7 authors, increases the average number of citations per article in biomedical research, chemistry and mathematics (Glänzel, 2002).…”
Section: : Collaboration and Citationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study on 20 university disciplinary areas, Franceschet and Costantini (2010) have shown that collaborative papers have a greater impact and are more valued by peer experts. Further, they found that both the impact and quality of papers are further enhanced when the author affiliations are heterogeneous.…”
Section: Collaborationmentioning
confidence: 99%
“…Still, there are some proved incentives for sharing the research outcomes on the web, e.g. higher citation impact of papers (Franceschet & Costantini, 2010). Compared to the traditional scientific dialogue within articles (Groth & Gurney, 2010) where most citations to publications occur after 3 years (often behind the paywall) and diminish after 10 years, the online conversation has the advantage of being more responsive and as well as more open to outsiders.…”
Section: Open Distributed Collaborationmentioning
confidence: 99%